Unusual 4p16.3 deletions suggest an additional chromosome region for the Wolf‐Hirschhorn syndrome–associated seizures disorder. Issue 6 (16th April 2014) - Zollino, Marcella; Orteschi, Daniela; Ruiter, Mariken; Pfundt, Rolph; Steindl, Katharina; Cafiero, Concetta; Ricciardi, Stefania; Contaldo, Ilaria; Chieffo, Daniela; Ranalli, Domiziana; Acquafondata, Celeste; Murdolo, Marina; et al.
Summary Objective Seizure disorder is one of the most relevant clinical manifestations in Wolf‐Hirschhorn syndrome (WHS) and it acts as independent prognostic factor for the severity of intellectual disability (ID). LETM1, encoding a mitochondrial protein playing a role in K+/H+ exchange and in Ca2+ homeostasis, is currently considered the major candidate gene. However, whether haploinsufficiency limited to LETM1 is enough to cause epilepsy is still unclear. The main purpose of the present research is to define the 4p chromosome regions where genes for seizures reside. Methods Comparison of our three unusual 4p16.3 deletions with 13 literature reports. Array‐comparative genomic hybridization (a‐CGH). Real‐time polymerase chain reaction (RT‐PCR) on messanger RNA (mRNA) of LETM1 and CPLX1. Direct sequencing of LETM1. Results Three unusual 4p16.3 deletions were detected by array‐CGH in absence of a obvious clinical diagnosis of WHS. Two of these, encompassing LETM1, were found in subjects who never had seizures. The deletions were interstitial, spanning 1.1 Mb with preservation of the terminal 1.77 Mb region in one case and 0.84 Mb with preservation of the terminal 1.07 Mb region in the other. The other deletion was terminal, affecting a 0.564 Mb segment, with preservation of LETM1, and it was associated with seizures and learning difficulties. Upon evaluating our patients along with literature reports, we noted that six of eight subjects with terminal 4p deletions preserving LETM1 had seizures, whereas seven of seven with interstitial deletions including LETM1 and preserving the terminal 1 Mb region on 4p did not. An additional chromosome region for seizures is suggested, falling within the terminal 1.5 Mb on 4p, not including LETM1. Significance We consider that haploinsufficiency not limited to LETM1 but including other genes acts as a risk factor for the WHS‐associated seizure disorder, according to a comorbidity model of pathogenesis. Additional candidate genes reside in the terminal 1.5 Mb region on 4p, most likely distal to LETM1. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.